Micro-content Generation Framework as a Learning Innovation - János Horváth Cz (In the Beginning was the Image: The Omnipresence of Pictures, 2016)
Young people today have established a new content consumption culture by the active, everyday use of content sharing sites. The time dedicated to particular content items has decreased, while the number of texts, images or other media items viewed in a given unit of time has increased. Technology poses no limit to “information gluttony”: state of-the-art Web 2.0 technologies facilitate connection to a continuous news feed. The basic economic principles also work here, however, as the value of ample resources is low. To compensate for the inflation of information value, an experiment was initiated to examine the potential of microcontent